Emerging evidence on Monkeypox: resurgence, global burden, molecular insights, genomics and possible management - Ruchi Sharma; Kow-Tong Chen; Kow-Tong Chen; Rohit Sharma (Frontiers in Cellular and Infection Microbiology, 2023)
An outbreak of monkeypox (encoded enveloped double stranded DNA), resurgence and expansion has emerged in early 2022, posing a new threat to global health. Even though, many reports are available on monkeypox, still a comprehensive updated review is needed. Present updated review is focused to fill the research gaps pertaining to the monkeypox, and an extensive search was conducted in a number of databases, including Google Scholar, Scopus, Web of Science, and Science Direct. Although the disease usually progresses self-limiting, some patients require admission for kidney injury, pharyngitis, myocarditis, and soft tissue super infections. There is no well-known treatment available yet; still there has been a push for the use of antiviral therapy and tecovirimat as a promising option when dealing with co-morbidities. In this study, we mapped and discussed the updates and scientific developments surrounding monkeypox, including its potential molecular mechanisms, genomics, transmission, risk factors, diagnosis, prevention, vaccines, treatment, possible plant-based treatment along with their proposed mechanisms. Each day, a growing number of monkeypox cases are reported, and more cases are expected in the near future. As of now, monkeypox does not have a well-established and proven treatment, and several investigations are underway to find the best possible treatment from natural or synthetic drug sources. Multiple molecular mechanisms on pathophysiological cascades of monkeypox virus infection are discussed here along with updates on genomics, and possible preventive and therapeutic strategies.